Utilization by finishing pigs of reconstituted sorghum grain treated with enzymes or enzymes plus a bacterial inoculant prior to ensiling - J I Heidker; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1988)
One hundred eight finishing pigs averaging 117 lb were used to evaluate the effects of adding enzymes with or without a bacterial inoculant to reconstituted sorghum grain used in swine diets. No differences were noted in gain, feed efficiency, or carcass characteristics as determined by ultrasonic scanning.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Reconstituted; Grain sorghum; Enzymes; Inoculant; Finishing pigs